The Inhibitory Effect Zingiber Offlcinale Extracts on Microorganisms whichAssociated with Biscuit. (Baghdad Science Journal, 2012)
The research aimed at studying the inhibitive effect of the hot watery dry and ethanolic ginger(85%) and fragrant oil which are added in concentrates of o.o25, o.o5o and 0.1g / 100g respectively in the growth of bacteria and molds. The results of the initial chemical diagnosis showed containment of ginger roots extract on. Alkaloids, Glycosides, Flavonoids and Suponins. The highest inhibitive effect of the bacteria reached the concentrate . 0.1% of the oil extract then the concentrate 0.050% of the ethanolic hot extract follows it. While 0.1% was the least inhibitive concentrate for the hot watery extract. But the inhibitive effect of the hot oily and alcoholic extracts in the numbers of molds colonies was 0.025%, when the concentrate 0.1% of the hot watery extract appeared the least inhibitive concentrate for molds. The ensual evaluation of the manufactured biscuit which is stored for fifteen weeks results showed the excel of the treatment A3 (concentrate 0.1%) of the hot ethanolic extract in the aualities of appearance , flavor and flakiness where it reached 5.800 indicates the efficievcy of the effective compounds in ginger in protecting from rancidity and oxidation during the storing period in comparison to the control treatment (without adding ginger) where it got 4.600, 4.600 and 5 respectively . when the treatments A1(0.0 25%), A2(0.050%) and O1(0.025%) got the least values where it reached 2.800, 3.800, 3.600 in the qualities of color, texture and general acceptance.